Ergodicity, Graphism, and Multimediality as Literary Strategies in the Literary Works by Serbian Authors - Božić, Snežana V. (Collection of Papers of the Faculty of Philosophy in Priština, 2023)
Starting with the explication of title terms derived from theories of ergodicity (E. Aarseth), new media and visual arts (Mitchell W. J. T., A. Hescher), i.e. from the practice of digital literature and graphic novel, this paper points to their increasingly significant presence within the framework of contemporary Serbian (printed) literature, which is observed as an outcome of the implications of the altered technological-communicational, socio-cultural, and economic contexts on the literary creation and the reception of literature. Are the strategies of ergodicity, graphism, and multimediality (present in the forms of nonlinearity, playability, interactivity, synthetic visual and narrative forms, cinematographic dynamics etc.) expressions of authentic artistic inspiration that seeks for new means of expression and finds them in the sphere of visual and digital, or products of the author’s desire to get closer to the reader and expand the circle of his addressees? Are we within the space of a literature experiment or are we talking about new, hybrid genres that are still a step above literature understood in the traditional sense? Are all the graphic and multimedia “extensions” of the narrative causing benefit or detriment of literature and overall aesthetic value? These are some of the questions that the paper seeks to answer through theoretical insights, as well as several brief analytical reviews of specific works taken as case studies, by authors S. Vladušić (Mi, izbrisani), T. Stupar Trifunović and T. Vidojević (More je bilo mirno), U. Krčadinac, L. Pašćanović, and М. Đedović (Bantustan: Atlas jednog putovanja).